1999
DOI: 10.1016/s0960-9822(99)80312-1
|View full text |Cite
|
Sign up to set email alerts
|

A missing metabolic pathway in the cattle tick Boophilus microplus

Abstract: Heme proteins are involved in a wide variety of biological reactions, including respiration, oxygen transport and oxygen metabolism [1]. The heme prosthetic group is synthesized in almost all living organisms except for a few pathogenic bacteria and trypanosomatids that use blood as food [2] [3]. There is a general belief that all nucleated animal cells synthesize heme [1] [4]. However, blood-feeding arthropods ingest enormous amounts of vertebrate blood in a single meal and the heme pathway has not been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 15 publications
(17 reference statements)
0
78
0
3
Order By: Relevance
“…It is plausible that the ancestral worm lost the genes responsible for heme biosynthesis due to a lack of selective pressure because the progenitor had access to heme either from a parasitized host or from a symbiotic relationship with another organism. Recent studies have shown that the cattle tick Boophilus microplus, a bloodsucking arthropod, relies on blood meals to acquire heme (41), and pathogenic human filarial nematodes as well as certain insects harbor the bacteria Wolbachia, an intracellular symbiont that has a mutualistic relationship with its host such that the nematode acquires endobacterial-derived metabolites (42,43). Indeed, the Wolbachia genome contains orthologs of genes for heme biosynthetic enzymes, suggesting that this endosymbiont has the ability to make heme.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that the ancestral worm lost the genes responsible for heme biosynthesis due to a lack of selective pressure because the progenitor had access to heme either from a parasitized host or from a symbiotic relationship with another organism. Recent studies have shown that the cattle tick Boophilus microplus, a bloodsucking arthropod, relies on blood meals to acquire heme (41), and pathogenic human filarial nematodes as well as certain insects harbor the bacteria Wolbachia, an intracellular symbiont that has a mutualistic relationship with its host such that the nematode acquires endobacterial-derived metabolites (42,43). Indeed, the Wolbachia genome contains orthologs of genes for heme biosynthetic enzymes, suggesting that this endosymbiont has the ability to make heme.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore quite surprising to find that R. microplus lacks the hemB enzyme, cannot synthesize heme and is therefore dependent on host-derived heme (Braz et al 1999). BLASTP analysis of hemB in 2011 indicated that no hemB homologs could be found for ticks, but were found in acariform mites (Mans, 2014).…”
Section: Heme the Centre Of Lifementioning
confidence: 99%
“…Other blood-feeding arthropods such as mosquitoes probably retain their ability to synthesize heme, since not all lifestages are obligatory blood-feeding. Assassin bugs are obligatory blood-feeders, but did not lose their ability to synthesize heme, although they may also utilize host-derived heme (Braz et al 1999). All stages of ticks (with some derived exceptions: see ecdysis section) are obligatory blood-feeders and could potentially derive all of their heme needs from their diet (Donohue et al 2009).…”
Section: Heme the Centre Of Lifementioning
confidence: 99%
“…Furthermore, R. microplus lacks the biosynthetic pathway for heme production and therefore acquires it from the blood meal (Braz et al, 1999 Anderson et al, 2008). These proteins have also been suggested to play a role in smooth muscle contraction of the midgut during feeding.…”
Section: Other Midgut-specific Proteinsmentioning
confidence: 99%